Ecological functions of neotropical amphibians and reptiles: a review - Cortes, Angela María; Instituto de investigaciones en Recursos Biológicos Alexander von Humboldt, Laboratory of Conservation Genetics, Bogotá, Colombia. Herpetology Laboratory group, Biology Department, Universidad del Valle, Cali-Colombia (Pontificia Universidad Javeriana, 2014)
Amphibians and reptiles (herps) are the most abundant and diverse vertebrate taxa in tropical ecosystems. Nevertheless, little is known about their role in maintaining and regulating ecosystems functions and, by extension, their potential value for supporting ecosystems services. Here, we review research on the ecological functions of Neotropical herps, in different sources (the bibliographic databases, book chapters, etc.). A total of 167 Neotropical herpetology studies published over the last four decades (1970 to 2014) were reviewed, providing information on more than 100 species that contribute to at least five categories of ecological functions: i) nutrient cycling; ii) bioturbation; iii) pollination; iv) seed dispersal, and v) energy flow through ecosystems and the mechanisms behind these, through the study of functional traits and analysis of ecological processes. Many of these functions provide key ecosystems, such as biological pest control, seed dispersal and water quality. By knowing and understanding the functions that perform the herps in ecosystems, management plans for cultural landscapes, restoration or recovery projects of landscapes that involve aquatic and terrestrial systems, development of comprehensive plans and detailed conservation of species and ecosystems may be structured in a more appropriate way. Besides information gaps identified in this review, this contribution explores these issues in terms of better understanding of key questions in the study of ecosystem services and biodiversity and, also, of how these services are generated.